Методология педагогики в современном образовании - Омельченко, А. В. (НТУ "ХПИ", 2013)
Весь педагогический процесс скрыто или явно пронизан методологическими предписаниями: от предельно общих до конкретных методических рекомендаций. В данной статье рассмотрены сущность, структура и функции методологии педагогики, определено место методологического компонента системы знаний в содержании высшего образования и обозначены способы его формирования.

The pedagogical process is permeated by the methodological orders: from utterly general to concrete methodical recommendations. In this article the essence, structure and functions of methodology in pedagogics were defined. The proper place for the methodological knowledge in shaping the content of education and the methods of its formation were outlined.
Methodology of pedagogics in modern education
Keywords: процесс педагогический; содержание образования; система знаний; pedagogical process; methodological knowledge; content of education